2008
DOI: 10.1002/app.28344
|View full text |Cite
|
Sign up to set email alerts
|

Study on the acidic hydrolysis process of poly(N‐vinylformamide/acrylonitrile) fiber

Abstract: A convenient method of preparing chelating fiber with amine groups on the fiber surface was developed. The precursor polymer of Poly(N-vinylformamide/acrylonitrile) (P(NVF/AN)) was synthesized via solution polymerization, using N-vinylforaimde as a functional monomer. The solution of P(NVF/AN) was spun through a wet spinning method and the precursor fiber was hydrolyzed in the hydrochloric acid solution to convert formamide moieties to the corresponding amine. The influence of hydrolytic conditions on hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Alkaline hydrolysis of acrylate/NVF copolymers generates insoluble lactam polymers caused by intramolecular neighbor group reactions . A similar behavior is observed during acidic hydrolysis of acrylonitrile/NVF where amidinium structure formation takes place …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Alkaline hydrolysis of acrylate/NVF copolymers generates insoluble lactam polymers caused by intramolecular neighbor group reactions . A similar behavior is observed during acidic hydrolysis of acrylonitrile/NVF where amidinium structure formation takes place …”
Section: Introductionsupporting
confidence: 55%
“…Numerous publications clearly indicate the excellent copolymerization abilities of NVF . The copolymerization of NVF with vinyl monomers possessing electron deficient CC double bonds such as acrylates, acrylamides, or maleates yields copolymers with alternating tendencies, while copolymerization with ethylene or vinyl esters forms random types of copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…This technique is applicable for the preparation of fibers containing various materials, such as activated carbon, 94 graphene, 95 multi-walled carbon nanotube, 96 titanium dioxide, 97 and platinum nanoparticle, 98 as well as chelating ligand. 99,100 Chelating fibers containing fine particulate CM-PEHA resin 101 and CM-PEI 102,103 were prepared based on this technique, and the potential of the chelating fibers for the solid-phase extraction of elements was investigated.…”
Section: Chelating Fibermentioning
confidence: 99%
“…PNVF has been applied in some practical uses, such as coating slips, petroleum recovery, hair care, protein release, fibers, and the drag reducing polymers. [32][33][34][35][36][37][38] Our previous study 13 showed that PNVF strongly interacts with SDS, and the cac of SDS in the presence of PNVF is ca. 3.0 mM.…”
Section: Introductionmentioning
confidence: 99%